PERENCANAAN DAN PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2015 DI DIREKTORAT PENGEMBANGAN KEMAHASISWAAN UNIVERSITAS SURABAYA - Suvina Lionnard; Eric Wibisono; Stefanus Soegiharto (CALYPTRA, 2018)
Directorate of Students Development is a department responsible forstudent activities in University of Surabaya. This research discusses the design of Quality Management System which is accordance to the requirements of ISO9001:2015 at Directorate of Students Development. The research started withidentifying gaps, determining improvement opportunities, implementing alternative solutions and evaluating the quality management system. The methodsused for this research are observation, interview, and document collection. The result of gap analysis between organization's existing condition compared to ISO 9001:2015 resulting in 52% conformity, 36% partial, and 12% nonconformity.Based on these assessments, there are some improvement opportunities that can be done such as identifying organization's stakeholders, creating quality objectives based on strategies, analyzing risks and the process of transfer knowledge. The evaluation of quality management system can be done by reviewing the system with the concept of seven principles of Quality Management System.